2019
DOI: 10.1002/anie.201904904
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Exciton Binding Energy of Donor–Acceptor‐Based Conjugated Polymers to Promote Charge‐Induced Reactions

Abstract: Exciton binding energy has been regarded as ac rucial parameter for mediating charge separation in polymeric photocatalysts.M inimizing the exciton binding energy of the polymers can increase the yield of charge-carrier generation and thus improve the photocatalytic activities,b ut the realization of this approach remains ag reat challenge. Herein, aseries of linear donor-acceptor conjugated polymers has been developed to minimizethe exciton binding energy by modulating the charge-transfer pathway. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
263
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 376 publications
(273 citation statements)
references
References 47 publications
8
263
1
1
Order By: Relevance
“…[21][22][23][24] Most photocatalysts so far have been inorganic materials, but organic photocatalysts have attracted growing attention 25 because they can be prepared from earth-abundant elements and their properties-and in particular their light absorption spectrum-can be tuned easily and continuously by co-polymerisation. [26][27][28][29][30][31][32][33][34] However, most polymer studies have been conned to the sacricial half-reaction that produces hydrogen only, and few organic photocatalysts have been developed for overall water splitting. Carbon nitrides have been coupled with WO 3 , which acts as an O 2 evolution photocatalyst in a Z-scheme system for overall water splitting, 26,27,35 but the efficiencies were limited by the commonly observed back reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Most photocatalysts so far have been inorganic materials, but organic photocatalysts have attracted growing attention 25 because they can be prepared from earth-abundant elements and their properties-and in particular their light absorption spectrum-can be tuned easily and continuously by co-polymerisation. [26][27][28][29][30][31][32][33][34] However, most polymer studies have been conned to the sacricial half-reaction that produces hydrogen only, and few organic photocatalysts have been developed for overall water splitting. Carbon nitrides have been coupled with WO 3 , which acts as an O 2 evolution photocatalyst in a Z-scheme system for overall water splitting, 26,27,35 but the efficiencies were limited by the commonly observed back reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[40] By contrast with CN, the fluorescence of Nb 2 O 5 /CN is partially quenched, suggestive of suppression for charge recombination. [41] Astonishingly, NSNOCN displays the lowest PL emission-peak intensity, strongly indicating that the formation of spatial charge-transfer cascades is highly conducive to the acceleration of charge transfer. Transient photocurrent responses further support such results.…”
Section: Resultsmentioning
confidence: 99%
“…[155,161,162] Common strategies to improve photocatalytic performance typically aim 1) to match the HOMO-LUMO to the thermodynamic requirements of the water redox reactions (driving forces for charge transfer), 2) to improve intermolecular packing and charge transport by enhancing the coplanarity of the polymer [163] or increasing the conjugation degree, [164] and 3) to increase the charge density in the system by introducing electron-rich units via copolymerization or blending donor and acceptor type polymers. [165] The work of Sachs et al showed that these properties are however not adequate to enhance the activity alone, but hydrophilicity of the polymer is crucial to favor electron transfer to protons. [166] Introducing hydrophilic units increased polaron yields thanks to the organization of water around the polymer, whose polarity accelerated the electron transfer step.…”
Section: Fuel Generation From An Aqueous Medium Via Photo or Electrocmentioning
confidence: 99%